Influence of age on conformation and weight of suckling kid carcass pieces - Guti?rrez, Delf?n; Enr?quez, Ana V.; Tuero, O.; Fraga, Luis Mateo (Cuban Journal of Agricultural Science, 2010)
Twenty crossbred Creole kids, non-weaned and with 60 and 90 d of age, were slaughtered to reveal the influence of slaughter age on the conformation of goat carcass and the weight of meat pieces. The kids were grazing for eight hours, regularly with their mothers. At night, they were in barns with mineral salts and water ad libitum. At the age scheduled, they were slaughtered. The slaughter liveweight (SLW), hot (HCW) and cold carcass weight (CCW), and the yields (HCY and CCY). Objective measures of carcass conformation and fat estimated were included in the study. The results showed a linear relationship of slaughter liveweight with carcass components, being superior in the coefficients for the hot and cold carcass weights, leg (0.96, P < 0.001), neck and depth of thorax (0.94, P < 0.001), rump width (0.92, P < 0.001), and weight of the rips (0.89, P < 0.001). With the advance of age, the hot and cold carcass slaughter weight, the hot carcass yield and the measures of the leg length (F), width of the rump (G), and thorax (Wr) also differed (P < 0.001, P < 0.05). The same occurred with the internal carcass length indices (L), the depth of the thorax (Th), as well as those of conformation (G/F, Wr/Th), which did not differ. In respect to the pelvic-renal fat, the lowest score (2.11) appeared in the youngest animals. In the meat pieces, the outcomes were analogous and, although they showed differences (P < 0.001), the oldest animals had heavier meat pieces. The shoulder showed, contrary to the rest of the meat pieces, an early development. It was concluded that it is necessary to use the carcass conformation and the weight of the meat pieces according to age as criterion to measure the amount of meat that could be expected from the animal. Key words: conformation, carcass, slaughter.